Postdiagnosis dietary factors, supplement use and breast cancer prognosis: Global Cancer Update Programme (CUP Global) systematic literature review and meta‐analysis. Issue 4 (24th October 2022) - Becerra‐Tomás, Nerea; Balducci, Katia; Abar, Leila; Aune, Dagfinn; Cariolou, Margarita; Greenwood, Darren C.; Markozannes, Georgios; Nanu, Neesha; Vieira, Rita; Giovannucci, Edward L.; Gunter, Marc J.; Jackson, Alan A.; et al.
Abstract: Little is known about how diet might influence breast cancer prognosis. The current systematic reviews and meta‐analyses summarise the evidence on postdiagnosis dietary factors and breast cancer outcomes from randomised controlled trials and longitudinal observational studies. PubMed and Embase were searched through 31st October 2021. Random‐effects linear dose‐response meta‐analysis was conducted when at least three studies with sufficient information were available. The quality of the evidence was evaluated by an independent Expert Panel. We identified 108 publications. No meta‐analysis was conducted for dietary patterns, vegetables, wholegrains, fish, meat, and supplements due to few studies, often with insufficient data. Meta‐analysis was only possible for all‐cause mortality with dairy, isoflavone, carbohydrate, dietary fibre, alcohol intake and serum 25‐hydroxyvitamin D (25(OH)D), and for breast cancer‐specific mortality with fruit, dairy, carbohydrate, protein, dietary fat, fibre, alcohol intake and serum 25(OH)D. The results, with few exceptions, were generally null. There was limited‐suggestive evidence that predefined dietary patterns may reduce the risk of all‐cause and other causes of death; that isoflavone intake reduces the risk of all‐cause mortality (relative risk (RR) per 2 mg/day: 0.96, 95% confidence interval (CI): 0.92‐1.02), breast cancer‐specific mortality (RR for high vs low: 0.83, 95% CI: 0.64‐1.07), and recurrence (RR for high vs low: 0.75, 95% CI: 0.61‐0.92); that dietary fibre intake decreases all‐cause mortality (RR per 10 g/day: 0.87, 95% CI: 0.80‐0.94); and that serum 25(OH)D is inversely associated with all‐cause and breast cancer‐specific mortality (RR per 10 nmol/L: 0.93, 95% CI: 0.89‐0.97 and 0.94, 95% CI: 0.90‐0.99, respectively). The remaining associations were graded as limited‐no conclusion. Abstract : What's new? To date, there are no evidence‐based nutritional guidelines specifically developed for breast cancer survivors due to a lack of knowledge. In this systematic review and meta‐analysis, the Global Cancer Update Programme evaluated the associations between postdiagnosis dietary patterns, dietary intakes, and supplements use and breast cancer outcomes among breast cancer survivors. The independent expert panel concluded that the evidence about potential associations remains limited (likelihood of causality: suggestive or no conclusion). Stronger evidence, contributed by intervention trials and/or well‐conducted observational studies, is needed before specific dietary recommendations for improving breast cancer prognosis can be made.